Fabrication of porous ceramics as clay/glass composite (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Nowadays porous ceramics are widely researched, becoming an increasingly marketable material in the world, mainly due to the wide possibilities of usage in different technical and technology industries. Porous ceramics are successfully used in the filtration and has a high potential of usage also in the production of heat insulation materials thus obtaining the material which combine high resistance that can compete with other heat insulation and constructive materials.Article reports a study of porous ceramics, which are produced using foamglass pellets as melting fillers, despite the fact that these additives are not frequently used as filler in traditional ceramic materials. The basis of this method is mixing fire resistant material with hard and melting substance.For the production of porous ceramics clay, hard filler, water and various sized foamglass pellets were used, thus allowing to determine optimal size of melting filler and thereby ensuring the necessary physical and mechanical properties of the obtained porous ceramic samples and required amount, size and division of pores.  Compressive strength tests were performed, as well as density and water absorption of the samples was determined.Obtained results of the study shows that ceramic materials, obtained within the research, have great potential of application for load-bearing constructions as constructive building materials, as well as insulation materials. Production of porous ceramics materials, where foamglass pellets are used as melting filler, allows to produce more effective ceramics, creating high added value for the final product.